Making multicultural education work - May, Stephen, 1962- (Language and education library, 1994)
Addresses the issue of the efficacy of multicultural education. May advocates the need for a more critically conceived approach to multicultural education. A case study - of Richmond Road School in Auckland, New Zealand - illustrates what can be achieved when this is effectively implemented.